Constitution and its interpretation - Kūris, Egidijus (Politologija, 1999)
In the article, it is oftentimes referred to the recent (1998) article in this journal by Aleksandras Dobryninas in which (on the basis of Aristotelian theory) the Constitution is defined both as a fundamental law of the state, and as the set of fundamental principles revealed inter alia through the interpretation process. After having stated that "it appears difficult to altercate on the theoretical sagacity of the ideas" postulated in the said article, the author indicates that there is a certain inconsistency which may lead to conclusions negating the given theoretical postulates. It is argued that the stability of the constitutional order should not be understood only in quantitative terms (such as the number of amendments to the "basic text" of the fundamental law) but that the potential of constitutional interpretation should also be taken into account.The result of the interpretation of the Constitution is the constitutional doctrine worked out by the Constitutional Court (or other courts of constitutional jurisdiction). It is argued that, unless the constitutional doctrine is included under the broad concept of the Constitution and awarded the same legal force as the "basic text" of the Constitutional Act, there is unavoidable a contradiction between the necessity to maintain the stability of the constitutional order and the necessity of having the Constitution up to date with the requirements of time. On the basis of the Constitutional Court of Lithuania, it is shown that, at the current stage of development, the constitutional doctrine is generated by virtue of the constitutional conflicts ruled by the Constitutional Court.So far, the Court has not yet interpreted most of the constitutional provisions, which leads to the conclusion that, in many fields of societal relations, the country has as little of "applicable" Constitution as it has of the constitutional jurisprudence.
Keywords: -